Preparation method of PEDOT: PSS poly-ampholyte composite material

The PEDOT:PSS@polyampholyte composite material was prepared by iCVD method, which solved the problems of slow response speed and low sensitivity of existing humidity-sensitive materials in high-precision humidity sensing, and realized a humidity sensor with high sensitivity and fast response.

CN120795388APending Publication Date: 2025-10-17FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510995098.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing humidity-sensitive materials have slow response speed and low sensitivity in high-precision humidity sensing, and their performance is poor at room temperature. Materials prepared by liquid phase method may damage the flexible substrate and affect the sensor performance.

Method used

PEDOT:PSS@polyampholyte composite material was prepared by iCVD method. A zwitterionic polymer was formed by copolymerization of DMAEMA and MAA, and the porosity was controlled by combining EGDMA crosslinking agent. PEDOT:PSS was spin-coated on the polymer surface to form a conductive path and realize hole-ion coupling.

Benefits of technology

The response performance of the humidity sensor is improved, with high sensitivity, small hysteresis and short recovery time, making it suitable for real-time humidity detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795388A_ABST
    Figure CN120795388A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of humidity-sensitive materials, and particularly relates to a preparation method of a PEDOT: PSS poly-ampholyte composite material. The preparation method comprises the following steps: preparing a hydrophilic polyampholyte by adopting an initiating chemical vapor deposition method (iCVD), and preparing the hydrophilic polyampholyte on the surface of a flexible polyimide interdigital electrode by taking dimethylaminoethyl methacrylate and methacrylic acid as hydrophilic monomers and ethylene glycol dimethacrylate as a cross-linking agent to form a polyampholyte polymer film; and then spin-coating a conductive polymer PEDOT: PSS on the surface of the film to successfully prepare the PEDOT: PSS poly-ampholyte composite material. The humidity sensor prepared from the PEDOT: PSS poly-ampholyte composite material has the advantages of high sensitivity, small lag, short recovery time and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of humidity-sensitive materials, and particularly relates to a preparation method of a PEDOT:PSS@polyampholyte composite material. BACKGROUND

[0002] In the field of humidity sensing, the selection of humidity-sensitive materials is crucial. Common humidity-sensitive materials include ceramics, metal oxides, and high molecular polymers. Ceramic materials are stable, but their response speed is slow and their sensitivity is relatively low, limiting their application in high-precision humidity sensing. Metal oxides exhibit good performance at high temperatures, but their sensing performance is poor at room temperature, which cannot meet the needs of daily environmental monitoring. Hydrophilic polymers still have some challenges in the field of humidity sensing: the thickness of hydrophilic polymers synthesized in liquid phase is difficult to control, which usually leads to the synthesis of thick coatings, which not only increases the use amount of materials, but also may affect the sensitivity of the sensor. At the same time, when the humidity-sensitive material prepared by the liquid phase method is combined with a flexible substrate, the use of solvent may damage the substrate and affect the overall performance of the sensor. SUMMARY

[0003] To solve the problems in the prior art, the application provides a preparation method of a PEDOT:PSS@polyampholyte composite material. The humidity sensor prepared by using the PEDOT:PSS@polyampholyte composite material has the advantages of high sensitivity, small hysteresis, short recovery time, etc.

[0004] To achieve the above-mentioned purpose, the application adopts the following technical solutions: In a first aspect, the application provides a preparation method of a PEDOT:PSS@polyampholyte composite material, comprising the following steps: The substrate is cleaned and treated, and the cleaned substrate is placed in an iCVD reaction chamber, and the iCVD reaction chamber is vacuumed to a first preset pressure; After DMAEMA, MAA, EGDMA and TBP are evaporated, they are introduced into the iCVD reaction chamber, and the iCVD reaction chamber is controlled to maintain a second preset pressure; The substrate is cooled to maintain a preset temperature; Under the conditions of the preset temperature and the second preset pressure, the radicals formed by the cracking of DMAEMA, MAA, EGDMA and TBP undergo polymerization reaction on the surface of the substrate to form a polyampholyte polymer film; A PEDOT:PSS solution is spin-coated on the surface of the polyampholyte polymer film, and the PEDOT:PSS@polyampholyte composite material is obtained after annealing treatment.

[0005] Preferably, the molar ratio of the DMAEMA, MAA and EGDMA is (1-16):(1-16):3, and the molar ratio of the DMAEMA and MAA is 1:1.

[0006] Preferably, the substrate is a flexible polyimide interdigital electrode.

[0007] Preferably, the evaporation temperatures of the DMAEMA, MAA, EGDMA and TBP are 45±10℃, 40±10℃, 60±10℃ and 30±10℃, respectively.

[0008] Preferably, the first preset pressure is 0-15 mTorr, and the second preset pressure is 500 mTorr.

[0009] Preferably, the preset temperature is 40±2℃.

[0010] Preferably, the spin coating condition is: spin coating at 2500-3500 rpm for 45-55 seconds.

[0011] Preferably, the annealing condition is: annealing at 75-85℃ for 5-8 min.

[0012] In a second aspect, the present application provides a PEDOT:PSS@polyampholyte composite material.

[0013] In a third aspect, the present application provides an application of the PEDOT:PSS@polyampholyte composite material in the field of humidity sensors.

[0014] Compared with the prior art, the present application has the following beneficial effects: In the present application, DMAEMA containing a tertiary amine group and MAA containing a carboxylic acid group are used as hydrophilic monomers, and are copolymerized by the iCVD method to form an amphoteric ion polymer. The positive and negative charge groups on the molecular chain of the amphoteric ion polymer can efficiently adsorb water molecules to form a dynamic hydration layer, thereby improving the humidity sensitivity. The porosity of the polymer can be controlled by a crosslinking agent EGDMA to balance the water absorption swelling property and the chemical mechanical stability. PEDOT:PSS is formed by spin coating to form a conductive path, and an ionic bond or a hydrogen bond is formed between the sulfonic acid group and the polar group of the polyampholyte. At the layered interface of the PEDOT:PSS and the polyampholyte, a new charge carrier is formed when the hole is transferred from the conductive chain of PEDOT to the ion group in the polyampholyte, the coupling of the hole and the ion is realized, and the response performance of the sensor is improved. BRIEF DESCRIPTION OF DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 Flow chart of the preparation of PEDOT:PSS@polyampholyte composite material of the present invention; Figure 2 (a) Schematic diagram of the preparation of a polyampholyte polymer film according to the present invention; Figure 2 (b) Flowchart of spin coating PEDOT:PSS on polyampholyte polymer film on the surface of flexible polyimide interdigitated electrode; Figure 3 Schematic diagram of iCVD polymerization reaction; Figure 4 FTIR spectra of the materials obtained in Examples 1 to 4; Figure 5 (a) SEM image of the flexible polyimide interdigitated electrode without polymer deposition; Figure 5 (b) SEM image of a 100 nm thin film deposited on the pores of a flexible polyimide interdigitated electrode. Figure 5 (c) SEM image of a 500 nm thin film deposited on the pores of a flexible polyimide interdigitated electrode. Figure 5 (d) SEM image of a 1000 nm thin film deposited on the pores of the flexible polyimide interdigitated electrode. Figure 6 (a) XPS spectrum of p(DMAEMA-co-MAA-co-EGDMA); Figure 6 (b) XPS spectrum of PEDOT:PSS@p(DMAEMA-co-MAA-co-EGDMA) (PEDOT:PSS treated three times); Figure 7 (a) is a low-magnification image of the substrate surface coated with PEDOT:PSS@p(DMAEMA-co-MAA-co-EGDMA) in Example 3; Figure 7 (b) is the distribution diagram of C element in the composite material of Example 3; Figure 7 (c) is the distribution diagram of the O element in the composite material of Example 3; Figure 7(d) is a map of the distribution of N element in the composite material of Example 3; Figure 7 (e) is a map of the distribution of S element in the composite material of Example 3; Figure 7 (f) is a map of the distribution of Au element in the composite material of Example 3; Figure 7 (g) is a map of the distribution of elements in the composite material of Example 3. DETAILED DESCRIPTION

[0017] To enable persons skilled in the art to understand the features and effects of the present application, the following is a general description and definition of the terms and phrases mentioned in the specification and claims. Unless otherwise specified, all technical and scientific words used in the text are the usual meanings understood by those skilled in the art of the present application, and in the event of conflict, the definitions in the specification shall prevail.

[0018] Theories or mechanisms described and disclosed herein, whether correct or not, should not be considered limiting the scope of the present application, i.e., the present application can be practiced without regard to any particular theory or mechanism.

[0019] Herein, all features defined in the form of numerical ranges or percentage ranges, such as values, amounts, contents and concentrations, are for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have encompassed and specifically disclosed all possible sub-ranges and individual numerical values within the range (including integers and fractions).

[0020] Herein, unless otherwise specified, "comprise", "include", "contain", "have", or similar words encompass the meaning of "consist of" and "consist essentially of", for example, "A comprises a" encompasses the meaning of "A comprises a and other" and "A comprises only a".

[0021] Herein, for the sake of brevity, all possible combinations of the technical features in each embodiment or example are not described. Therefore, as long as the combinations of the technical features do not contradict each other, the technical features in each embodiment or example can be combined arbitrarily, and all possible combinations should be considered as the scope of the present specification.

[0022] Initiation chemical vapor deposition (iCVD) is an advanced polymer thin film preparation technology, which is to polymerize monomers in gas phase on the surface of the substrate under the action of initiator, and has the advantages of low temperature deposition (usually <100℃), no solvent, and accurate control of film thickness and chemical composition. The iCVD method can be used to prepare nanoscale polyamphoteric electrolyte films on the substrate at low temperature, and the integrity of the substrate is maintained. Secondly, by accurately controlling the monomer ratio and crosslinking degree, the hydrophilicity and stability of the material can be optimized. In addition, the surface functional groups of the polymer prepared by the iCVD method are complete, and the PEDOT:PSS spin-coated subsequently can form a stable interfacial bond, thereby synergistically improving the humidity sensing performance of the composite material.

[0023] The application will be further described in detail below with reference to the accompanying drawings: The first object of the present application is to provide a preparation method of PEDOT:PSS@polyamphoteric electrolyte composite material, as shown in (a) and (b), comprising the following steps: Figure 1 、 Figure 2 (a) (b) shown, comprising the following steps: The substrate is ultrasonically cleaned and then rinsed with anhydrous ethanol to remove surface impurities. The cleaned substrate is placed in the iCVD reaction chamber, and a vacuum pump is used to evacuate the iCVD reaction chamber to 0-15 mTorr; The hydrophilic monomers dimethylaminoethyl methacrylate (DMAEMA), methacrylic acid (MAA), crosslinking agent ethylene glycol dimethacrylate (EGDMA), and initiator tert-butyl peroxide (TBP) are evaporated at 45±10℃, 40±10℃, 60±10℃ and 30±10℃ respectively, and then introduced into the iCVD reaction chamber. The butterfly valve is used to control the iCVD reaction chamber to maintain 500 mTorr; The substrate is cooled by circulating cooling water to maintain the substrate at 40±2℃; Under the conditions of 40±2℃ and 500 mTorr, the initiator TBP is introduced into the iCVD reaction chamber, and the nickel-chromium alloy heating wire in the chamber is cracked into free radicals, and then the DMAEMA, MAA and EGDMA on the surface of the substrate are polymerized to form a polyamphoteric electrolyte polymer film; The PEDOT:PSS solution is spin-coated on the surface of the polyamphoteric electrolyte polymer film at a speed of 2500-3500 rpm, and the spin-coating time is 45-55 seconds. After annealing at 75-85℃ for 5-8min, the PEDOT:PSS@polyamphoteric electrolyte composite material is obtained.

[0024] The present application successfully prepares a high-performance PEDOT:PSS@polyampholyte composite material by an initiated chemical vapor deposition (iCVD) method combined with a spin coating process. Figure 3 As shown in the formula, DMAEMA (containing a tertiary amine group) and MAA (containing a carboxylic acid group) are used as monomers to form an amphoteric ion polymer network by iCVD copolymerization, and the positive and negative charge groups (-N + / -COO - ) on the molecular chain can efficiently adsorb environmental water molecules and form a dynamic hydration layer through hydrogen bonding, thereby significantly improving the humidity sensitivity of the material. Meanwhile, the introduction of the crosslinking agent EGDMA can control the porosity of the polymer network, balancing the water absorption swelling property and the chemical mechanical stability. The PEDOT:PSS on the surface is spin-coated to form a conductive path, and the sulfonic acid groups of PSS - form a hole-ion coupling interface with the polar groups of the polyampholyte, thereby improving the response performance of the sensor. The temperature of the substrate and the high temperature of the heating wire in the chamber can form a temperature gradient, which is conducive to the adsorption and polymerization of radicals and monomers on the surface of the interdigital electrode, and the deposition of nanoscale polymers. Spin coating ensures that the PEDOT:PSS solution penetrates into the surface layer micropores of the polyampholyte, and annealing removes residual solvents and promotes the crystallization of PEDOT chains, thereby improving the conductivity. In addition, by adjusting the number of spin coating times, the thickness of the conductive layer can be flexibly adjusted to adapt to different sensitivity requirements.

[0025] The molar ratio of DMAEMA, MAA and EGDMA is (1-16): (1-16): 3, and the molar ratio of DMAEMA and MAA is 1:1. This ratio promotes good compatibility with the PEDOT:PSS conductive layer, so that the composite material can fully exert the humidity sensitivity of the amphoteric electrolyte and the charge transport advantage of the conductive polymer, thereby obtaining a synergistically enhanced sensing performance. At the same time, the positive and negative charge groups in the material are in perfect balance, which not only ensures excellent hydrophilic performance, but also forms a stable molecular structure.

[0026] The substrate is a flexible polyimide (PI) interdigital electrode. The polyimide substrate has excellent flexibility, thermal stability and chemical inertness, and can adapt to various bending deformations and complex environments. Its porous structure is conducive to the rapid diffusion of water molecules, thereby improving the response speed of the sensor.

[0027] The second object of the present application is to provide a PEDOT:PSS@polyampholyte composite material, which has a hole-ion dual conduction mechanism, relies on the hole transport of PEDOT:PSS in the low humidity region, and enhances the response through the ion migration of the polyampholyte in the high humidity region, thereby solving the problem of insufficient electrical performance of traditional high polymer materials.

[0028] The third object of the present application is to provide an application of the PEDOT:PSS@polyampholyte composite material in the field of humidity sensors. The sensor prepared by using the PEDOT:PSS@polyampholyte composite material has the advantages of high sensitivity, small hysteresis, short recovery time, etc., and has a significant advantage in the field of real-time humidity detection.

[0029] The present application is further described in conjunction with the following specific examples. It should be understood that these examples are intended to illustrate the present application and are not intended to limit the scope of the present application. Furthermore, it should be understood that various modifications and changes can be made by those skilled in the art upon reading the contents of the present application, and such equivalent forms are also within the scope of the appended claims.

[0030] The following examples use conventional apparatus in the art. The experimental methods in the following examples, unless otherwise specified, are generally carried out under conventional conditions, or under the conditions recommended by the manufacturer. In the following examples, various raw materials are used, unless otherwise specified, and conventional commercially available products are used, which are conventional specifications in the art. In the specification of the present application and in the following examples, unless otherwise specified, "%" means weight percent, "parts" means weight parts, and the ratio means weight ratio.

[0031] Example 1 The flexible polyimide interdigital electrode was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode was placed in the iCVD reaction chamber, and a vacuum pump was used to vacuum the iCVD reaction chamber to 15 mTorr; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 45℃, 40℃, 60℃ and 30℃ respectively and introduced into the iCVD reaction chamber, and the iCVD reaction chamber was maintained at 500 mTorr by butterfly valve control; wherein the molar ratio of DMAEMA, MAA and EGDMA is 1:1:3; The flexible polyimide interdigital electrode was cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 40℃; Under the conditions of 40℃ and 500 mTorr, the initiator TBP was cracked into free radicals by the 280℃ nichrome heating wire in the chamber, and polymerization reaction occurred between the free radicals and DMAEMA, MAA and EGDMA on the surface of the flexible polyimide interdigital electrode, forming a polyampholyte polymer film; A PEDOT:PSS solution was spin-coated on the surface of the polyampholyte polymer film at a speed of 3000 rpm, and the spin-coating time was 50 seconds. After annealing at 80℃ for 5 minutes, a PEDOT:PSS@polyampholyte composite material was obtained.

[0032] Example 2 The flexible polyimide interdigital electrode was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode was placed in the iCVD reaction chamber, and the iCVD reaction chamber was vacuumed to 15 mTorr using a vacuum pump; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 45°C, 40°C, 60°C and 30°C respectively and introduced into the iCVD reaction chamber, and the iCVD reaction chamber was maintained at 500 mTorr by controlling the butterfly valve; wherein the molar ratio of DMAEMA, MAA and EGDMA is 4:4:3; The flexible polyimide interdigital electrode was cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 40°C; Under the conditions of 40°C and 500 mTorr, the initiator TBP was cracked into free radicals by the 280°C nichrome heating wire in the chamber, and polymerization reaction occurred on the surface of the flexible polyimide interdigital electrode with DMAEMA, MAA and EGDMA, forming a polyamphoteric electrolyte polymer film; A PEDOT:PSS solution was spin-coated on the surface of the polyamphoteric electrolyte polymer film at a speed of 3000 rpm for 50 seconds, and after annealing at 80°C for 5 minutes, a PEDOT:PSS@polyamphoteric electrolyte composite material was obtained.

[0033] Example 3 The flexible polyimide interdigital electrode was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode was placed in the iCVD reaction chamber, and the iCVD reaction chamber was vacuumed to 15 mTorr using a vacuum pump; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 45°C, 40°C, 60°C and 30°C respectively and introduced into the iCVD reaction chamber, and the iCVD reaction chamber was maintained at 500 mTorr by controlling the butterfly valve; wherein the molar ratio of DMAEMA, MAA and EGDMA is 8:8:3; The flexible polyimide interdigital electrode was cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 40°C; Under the conditions of 40°C and 500 mTorr, the initiator TBP was cracked into free radicals by the 280°C nichrome heating wire in the chamber, and polymerization reaction occurred on the surface of the flexible polyimide interdigital electrode with DMAEMA, MAA and EGDMA, forming a polyamphoteric electrolyte polymer film; The PEDOT:PSS solution was spin-coated on the surface of the polyampholyte polymer film at a speed of 3000 rpm, the spin-coating time was 50 seconds, and the PEDOT:PSS@polyampholyte composite was obtained after annealing at 80°C for 5 minutes.

[0034] Example 4 The flexible polyimide interdigital electrode was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode was placed in the iCVD reaction chamber, and a vacuum pump was used to vacuum the iCVD reaction chamber to 15 mTorr; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 45°C, 40°C, 60°C and 30°C respectively and introduced into the iCVD reaction chamber, and the iCVD reaction chamber was maintained at 500 mTorr by a butterfly valve; wherein the molar ratio of DMAEMA, MAA and EGDMA is 16:16:3; The flexible polyimide interdigital electrode was cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 40°C; Under the conditions of 40°C and 500 mTorr, the initiator TBP was cracked into free radicals by the 280°C nichrome heating wire in the chamber, and polymerization reaction occurred on the surface of the flexible polyimide interdigital electrode with DMAEMA, MAA and EGDMA, forming a polyampholyte polymer film; The PEDOT:PSS solution was spin-coated on the surface of the polyampholyte polymer film at a speed of 3000 rpm, the spin-coating time was 50 seconds, and the PEDOT:PSS@polyampholyte composite was obtained after annealing at 80°C for 5 minutes.

[0035] Example 5 The flexible polyimide interdigital electrode was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode was placed in the iCVD reaction chamber, and a vacuum pump was used to vacuum the iCVD reaction chamber to 0 mTorr; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 35°C, 30°C, 50°C and 20°C respectively and introduced into the iCVD reaction chamber, and the iCVD reaction chamber was maintained at 500 mTorr by a butterfly valve; wherein the molar ratio of DMAEMA, MAA and EGDMA is 1:1:1; The flexible polyimide interdigital electrode was cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 42°C; The initiator TBP is cracked into free radicals by 300℃ nickel-chromium alloy heating wire in the chamber at 42℃ and 500 mTorr, and polymerization reaction occurs between DMAEMA, MAA and EGDMA on the surface of the flexible polyimide interdigital electrode to form a polyampholyte polymer film; A PEDOT:PSS solution is spin-coated on the surface of the polyampholyte polymer film at a speed of 2500 rpm, the spin-coating time is 55 seconds, and the PEDOT:PSS@polyampholyte composite material is obtained after annealing at 75℃ for 8 min.

[0036] Example 6 The flexible polyimide interdigital electrode is ultrasonically cleaned and then rinsed with anhydrous ethanol to remove surface impurities, and the cleaned flexible polyimide interdigital electrode is placed in the iCVD reaction chamber, and a vacuum pump is used to vacuum the iCVD reaction chamber to 10 mTorr; The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP are evaporated at 55℃, 50℃, 70℃ and 40℃ respectively, and then introduced into the iCVD reaction chamber, and the iCVD reaction chamber is maintained at 500 mTorr by butterfly valve control; wherein the molar ratio of DMAEMA, MAA and EGDMA is 10:10:3; The flexible polyimide interdigital electrode is cooled by circulating cooling water to maintain the flexible polyimide interdigital electrode at 38℃; The initiator TBP is cracked into free radicals by 350℃ nickel-chromium alloy heating wire in the chamber at 38℃ and 500 mTorr, and polymerization reaction occurs between DMAEMA, MAA and EGDMA on the surface of the flexible polyimide interdigital electrode to form a polyampholyte polymer film; A PEDOT:PSS solution is spin-coated on the surface of the polyampholyte polymer film at a speed of 3500 rpm, the spin-coating time is 45 seconds, and the PEDOT:PSS@polyampholyte composite material is obtained after annealing at 85℃ for 6 min.

[0037] During the reaction, the thickness of the polymer deposited on the surface of the flexible polyimide interdigital electrode of Examples 1-4 is monitored in real time by a He-Ne laser interference device with a wavelength of 633 nm; and the polymer film morphology is observed using a scanning electron microscope (SEM); the FTIR spectrum of the polymer is measured in transmission mode using a Fourier transform infrared spectrometer (FTIR), the wavelength is set to 4000-400 cm-1, and the scanning number is 64, which is used to analyze the functional groups contained in the polymer coating, and the results are as follows:Figure 4 The crosslinking degree was further calculated, and the results are shown in Table 1: Table 1 Deposition conditions and performance data of polymers of Examples 1-4

[0038] The polymers prepared in Examples 1-4 have different crosslinking degrees, and the concentrations of anions and cations inside the polyamphoteric electrolyte thin films with different crosslinking degrees are different. The ions inside the polymer work together with PEDOT:PSS. When the humidity in the environment reaches a certain threshold, water vapor can fully activate the adsorption sites inside the thin film. The ion transport and hole transport work together to greatly improve the sensitivity and response of the prepared sensor. Second, the present application calculates the crosslinking degree of the polymer by peak fitting at the carbonyl group by FTIR. As the crosslinking degree decreases, the hydrophilicity of the polyamphoteric electrolyte surface increases, but the water stability of the thin film decreases. Too low crosslinking degree will make the contact angle of the thin film significantly increase after water washing.

[0039] In addition, the present application prepared thin films with different thicknesses, such as Figure 5 As shown in (a)-(d), when the thin film is deposited to 100 nm, most of the pores on the surface of the flexible polyimide interdigital electrode can still be seen. When the deposition thickness of the thin film is 500 nm and 1000 nm, the pores are gradually covered, which is not conducive to the transmission of water molecules.

[0040] Performance detection: The silicon wafer (the substrate is a silicon wafer to obtain XPS characterization results) was ultrasonically cleaned and rinsed with anhydrous ethanol to remove surface impurities. The cleaned silicon wafer was placed in the iCVD reaction chamber, and a vacuum pump was used to vacuum the iCVD reaction chamber to 15 mTorr. The hydrophilic monomers DMAEMA, MAA, EGDMA and TBP were evaporated at 45℃, 40℃, 60℃ and 30℃ respectively and then introduced into the iCVD reaction chamber. The iCVD reaction chamber was maintained at 500 mTorr by butterfly valve control. The molar ratio of DMAEMA, MAA and EGDMA was 8:8:3. The silicon wafer was cooled by circulating cooling water to maintain the silicon wafer at 38℃. At 38℃ and 500 mTorr, the initiator TBP was cracked into free radicals by the nichrome heating wire in the chamber, and polymerization reaction occurred between DMAEMA, MAA and EGDMA on the surface of the silicon wafer, forming a polyamphoteric electrolyte polymer thin film. A PEDOT:PSS solution was spin-coated on the surface of the polyamphoteric electrolyte polymer thin film at a speed of 3000 rpm for 50 seconds, and spin-coated three times. After annealing at 80℃ for 5 minutes, a PEDOT:PSS@polyamphoteric electrolyte composite material was obtained.

[0041] The polyampholyte polymer films p(DMAEMA-co-MAA-co-EGDMA) and PEDOT:PSS@p(DMAEMA-co-MAA-co-EGDMA) (PEDOT:PSS solution was spin-coated three times) deposited on silicon wafers were tested and their XPS spectra were obtained. Figure 6 (a) and Figure 6 As shown in (b), the XPS spectra all show the presence of C, N and O elements. However, compared with the copolymer, the composite material PEDOT:PSS@p(DMAEMA- co -MAA- co Significant S content was detected in the PEDOT:PSS (-EGDMA) copolymer, while the N content decreased and the O content increased. This is because when PEDOT:PSS was spin-coated on the copolymer surface, the N was located in the polymer layer beneath the PEDOT, resulting in a reduced spectral intensity corresponding to N in the composite. The increased O peak intensity in the composite is due to the presence of O in the PEDOT:PSS, while the presence of S indicates that PEDOT was successfully introduced to the polymer surface. The peaks at 1073 eV and 497.2 eV in the composite are Na, originating from the sodium polystyrene sulfonate in the PEDOT:PSS.

[0042] For polymer films and composite materials on the surface of flexible polyimide interdigitated electrodes, the distribution of elements is analyzed by EDS spectrometer. Figure 7 As shown in (a) to (f), C, O, S, and N are mainly derived from the copolymer p(DMAEMA- co -MAA- co -EGDMA) (C, O, N) and the conductive polymer PEDOT:PSS (C, O, S), the polymer is coated on the electrode surface, as evidenced by the three elements covering the entire interface. C is also distributed in the electrode, indicating that the polymer covers the entire electrode. The C outside the electrode is mainly derived from the polyimide PI film, and S is derived from PEDOT:PSS. It is more distributed in the electrode, which may be easier to form a film on the electrode that is higher than the substrate during the spin coating process. Figure 7 As shown in (g), Au and Ni come from the electrode part on the flexible polyimide interdigitated electrode, and the S atom content in the total energy spectrum is 0.3%, indicating that PEDOT:PSS is successfully spin-coated on the polymer surface.

[0043] A humidity sensor was prepared using the PEDOT:PSS@polyampholyte composite material prepared in Example 3, and the performance was compared with other representative composite humidity sensors, as shown in Table 2: Table 2 Performance data of humidity sensors prepared by the present invention and other humidity sensors

[0044] In summary, due to the porous structure of the PI substrate and the rapid desorption of water molecules promoted by the zwitterions in the polyampholyte, the sensor prepared by the application has the advantages of high sensitivity, small hysteresis, short recovery time, etc., and has a significant advantage in the field of real-time humidity detection.

[0045] The above only the preferred embodiments of the present application, and is not intended to limit the present application, for those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a PEDOT:PSS@polyampholyte composite material, characterized in that: The following steps are involved: Cleaning the substrate, placing the cleaned substrate in an iCVD reaction chamber, and evacuating the iCVD reaction chamber to a first preset pressure; DMAEMA, MAA, EGDMA and TBP are evaporated and introduced into the iCVD reaction chamber, and the iCVD reaction chamber is controlled to maintain a second preset pressure; Cooling the substrate to maintain the substrate at a preset temperature; Under the conditions of the preset temperature and the second preset pressure, the free radicals formed by the decomposition of the DMAEMA, MAA, EGDMA and TBP undergo a polymerization reaction on the surface of the substrate to form a polyampholyte polymer film; A PEDOT:PSS solution is spin-coated on the surface of the polyampholyte polymer film, and the PEDOT:PSS@polyampholyte composite material is obtained after annealing.

2. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The molar ratio of the DMAEMA, MAA and EGDMA is (1-16):(1-16):3, and the molar ratio of the DMAEMA and MAA is 1:

1.

3. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The substrate is a flexible polyimide interdigitated electrode.

4. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The evaporation temperatures of DMAEMA, MAA, EGDMA and TBP are 45±10°C, 40±10°C, 60±10°C and 30±10°C, respectively.

5. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The first preset pressure is 0-15 mTorr; the second preset pressure is 500 mTorr.

6. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The preset temperature is 40±2°C.

7. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The spin coating conditions are: spin coating at 2500-3500 rpm for 45-55 seconds.

8. The method for preparing a PEDOT:PSS@polyampholyte composite material according to claim 1, characterized in that: The annealing treatment conditions are: annealing at 75-85° C. for 5-8 minutes.

9. A PEDOT:PSS@polyampholyte composite material, characterized in that: The method according to claims 1 to 8 is used to prepare the present invention.

10. Use of the PEDOT:PSS@polyampholyte composite material according to claim 9 in the field of humidity sensors.